New fields expressions of a traveling wave circular loop antenna - Hamed , Sameir M.Ali; Bashir, Saad Osman (IEEE, 2013)
A technique that is based on spherical wave functions expansion for the free space Green’s function is used to derive exact near and far electromagnetic fields expressions for traveling wave circular loop antennas (TW-CLAs) with arbitrary phase change. These expressions describe separately electromagnetic fields inside and outside a sphere that generated when the loop revolves about its diameter. This makes the investigation of fields in the near region and inside the loop antenna simpler. Furthermore, a simplified expressions for the magnetic fields along the axis of the antenna and the known far-fields expressions for TW-CLA are obtained as special cases of the general field expressions presented in this paper.